2018
DOI: 10.1088/1475-7516/2018/09/030
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear perturbations from the coupling of the inflaton to a non-Abelian gauge field, with a focus on Chromo-Natural Inflation

Abstract: Several models of inflation employing a triplet of SU(2) vectors with spatially orthogonal vacuum expectation values (VEVs) have been recently proposed. One (tensor) combination t of the vector modes is amplified in some momentum range during inflation. Due to the vector VEVs, this combination mixes with gravitational waves (GW) at the linear level, resulting in a GW amplification that has been well studied in the literature. Scalar perturbations in this class of models have been so far studied only at the lin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 78 publications
(161 reference statements)
3
55
0
Order By: Relevance
“…In this case, if we ignore the contributions to the elements of the matrices in (3.10) that arise from integrating out the metric perturbations (namely, if we set to zero the metric perturbations by hand), one obtains the set of equations written for instance in eqs. (3.17) of [46]. As explicitly proven in [43], adding and then integrating out the metric perturbations provides additional contributions to the matrices C, K, Ω 2 , and then to the equation of motions, which are suppressed by higher order of the slow roll parameters with respect to the leading terms present in eqs.…”
Section: Scalar Sectormentioning
confidence: 82%
See 3 more Smart Citations
“…In this case, if we ignore the contributions to the elements of the matrices in (3.10) that arise from integrating out the metric perturbations (namely, if we set to zero the metric perturbations by hand), one obtains the set of equations written for instance in eqs. (3.17) of [46]. As explicitly proven in [43], adding and then integrating out the metric perturbations provides additional contributions to the matrices C, K, Ω 2 , and then to the equation of motions, which are suppressed by higher order of the slow roll parameters with respect to the leading terms present in eqs.…”
Section: Scalar Sectormentioning
confidence: 82%
“…This conclusion, however, does not account for the inflaton perturbations that can be produced at the nonlinear level by the t L mode. The power spectrum of these nonlinear scalar perturbations was computed only recently in the CNI model [46], where it was shown that these perturbations can be greater than the ones obtained by the linearized theory for a wide range of parameters. In this work we have repeated the same computation for the spectator model of [55].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Refs. [22,56], the primordial black hole production remains irrelevant in the parameter space in question.…”
Section: Cmb Observations Gravitational Waves and Primordial Black Hmentioning
confidence: 99%